Comparative analysis of global and Chinese trends in the burden of ischemic stroke attributable to secondhand smoke from 1990–2021 - Xiao Zhou; Jiaming Liu; Xin Li (Tobacco Induced Diseases)
Introduction Ischemic stroke (IS) represents a major health burden in China, and tobacco control is recognized as a practical and effective strategy to alleviate this impact. This study examines the influence of secondhand smoke (SHS) on the IS burden in China from 1990–2021.